Internal self-assessments in higher education based on interprocess relationships for university management - Ruiz Gutiérrez, Anisia (2022)
The Evaluation and Accreditation System of Higher Education Institutions in Cuba, aims to check the quality of management in the processes developed by the university and the relationship between them. To achieve these purposes there are processes that contribute to continuous improvement, if carried out with professionalism and quality, such as internal institutional selfassessments, based on interprocess relationships. However, the interrelation between the procedures that make it up, the direct observation of these academic exercises at the University of Ciego de Ávila (UNICA), the interviews and questionnaires applied to the participants, have shown deficiencies in the actions of management staff and professors for its realization, when planning, executing and controlling it as an instrument that contributes to the reality of the university context and that contributes to the solution of the determined difficulties. These reasons justify the need to propose a procedure for the realization of internal selfassessments in Higher Education Institutions, based on the interprocess relationship, so that it constitutes a methodological guide for its development and its subsequent evaluation of relevance. The results achieved with its introduction have contributed to increasing the efficiency and effectiveness of university management.